Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
Home  >>  CBSE XII  >>  Math  >>  Model Papers
0 votes

Solve \( 2tan^{-1}(cos \: x)=tan^{-1}(2 cosec \: x)\)

This question is Q.No 13 of misc ch 2
Can you answer this question?

1 Answer

0 votes
  • \( 2tan^{-1}y=tan^{-1}\large\frac{2y}{1-y^2}\:\:|y|<1\)
  • \(1-cos^2x=sin^2x\)
Given $2tan^{-1} (cos x) = tan^{-1} (2\, cosec\, x)$
By taking $y=cosx$, we get \(\large \frac{2y}{1-y^2}\)\(=\large \frac{2cosx}{1-cos^2x}\)\(=\large\frac{2cosx}{sin^2x}\)
\(\Rightarrow\: 2tan^{-1}cosx=tan^{-1}\large\frac{2cosx}{sin^2x}\)
Since L.H.S. = R.H.S., \( tan^{-1} \large \frac{2cosx}{1-cos^2x} \)\( = tan^{-1}(2cosecx)\)
\( \Rightarrow \large \frac{2cosx}{sin^2x}\)\(=2\: cosecx\)
\(\Rightarrow cosx=sin^2x.cosecx=sin^2x.\large \frac{1}{sinx}\)
\( \Rightarrow cosx\;sinx=sin^2x\)
\( \Rightarrow cosx=sinx\) \( \Rightarrow x=\large\frac{\pi}{4}\)
answered Mar 1, 2013 by thanvigandhi_1
edited Mar 18, 2013 by rvidyagovindarajan_1
Ask Question
student study plans
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App